Managing a change : case history of a bumiputera entrepreneur - Jemain, Johari (1997)
This study seeks to understand what an individual did, in the entrepreneurial processes that he underwent, when he entered the world of entrepreneurship. Specifically, the objectives were 1) to identify the processes in the individual's entrepreneurship development, 2) to know how the entrepreneur handle the changes in his entrepreneurial life, and 3) to identify the profile of the entrepreneur. The life period of the Bumiputera understudied covered the time prior to his leaving the salaried job until his business venture became profitable. A historical case study design was utilised. Three in-depth interviews of the informant were made and a two month field observation of the informant was done. All the interviews were tape recorded and transcribed. The daily observations were recorded. The data were then inductively analysed.